2(2x-5)-3+2=x+9

Simple and best practice solution for 2(2x-5)-3+2=x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-5)-3+2=x+9 equation:


Simplifying
2(2x + -5) + -3 + 2 = x + 9

Reorder the terms:
2(-5 + 2x) + -3 + 2 = x + 9
(-5 * 2 + 2x * 2) + -3 + 2 = x + 9
(-10 + 4x) + -3 + 2 = x + 9

Reorder the terms:
-10 + -3 + 2 + 4x = x + 9

Combine like terms: -10 + -3 = -13
-13 + 2 + 4x = x + 9

Combine like terms: -13 + 2 = -11
-11 + 4x = x + 9

Reorder the terms:
-11 + 4x = 9 + x

Solving
-11 + 4x = 9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-11 + 4x + -1x = 9 + x + -1x

Combine like terms: 4x + -1x = 3x
-11 + 3x = 9 + x + -1x

Combine like terms: x + -1x = 0
-11 + 3x = 9 + 0
-11 + 3x = 9

Add '11' to each side of the equation.
-11 + 11 + 3x = 9 + 11

Combine like terms: -11 + 11 = 0
0 + 3x = 9 + 11
3x = 9 + 11

Combine like terms: 9 + 11 = 20
3x = 20

Divide each side by '3'.
x = 6.666666667

Simplifying
x = 6.666666667

See similar equations:

| b^3-4b^2=21b | | -16=(-x) | | 9f+2f= | | 7v+4v= | | -38-(-14)= | | ln(8-x)=ln(3x-2)+ln(x+2) | | -6z+8=-13 | | y=.66x-1.25 | | 1.5y-12=60 | | ln(8-x)=ln(3x-2)+ln(x-2) | | 8(3x-19)=15x+7 | | .5(4x+1)(3x)=27 | | -m+2n=3 | | 4-10.00+4=44 | | 0.04c=5 | | 3-2y=-8 | | 5r^2-44r+120=-50+11r | | -x+7=-13 | | 16-a=-14 | | 11=15t+5t^2 | | x+ay=byequals | | 2x^5-162=0 | | 8h^2-18hj-5j^2= | | 1.5y-12*4=180 | | (11+5v)-(13v+2)= | | 8-1x+4x=2-3x | | 17+2(2n-12)=1 | | -6m+4=2 | | -2+3(-1)=-(-1+6) | | -10y+18=-(5y-7)+6y | | 12*-3.8-10=4*-3.8-32-3*-3.8 | | 16-8n+3+2n=45 |

Equations solver categories